Comparison of induction chemotherapy plus concurrent chemoradiotherapy and induction chemotherapy plus radiotherapy in locally advanced nasopharyngeal carcinoma. (December 2020) - Wang, Qiaoli; Xu, Guoqiang; Xia, Yaoxiong; Zuo, Jia; Zeng, Guilin; Xue, Zhihong; Cao, Ruixue; Xiong, Wei; Li, Wenhui
Abstract: Background: Induction chemotherapy plus concurrent chemoradiotherapy (IC + CCRT) is a standard treatment regimen for locally advanced nasopharyngeal carcinoma (LA-NPC). However, the increased acute toxicity of this intensified chemotherapy may counteract its efficacy. The results of studies focusing on the omission of concurrent chemotherapy (CC) regimens are controversial. Therefore, we carried out a meta-analysis to elucidate the efficacy and toxicity of IC + CCRT versus IC plus radiotherapy alone (IC + RT) for LA-NPC. Methods: Studies available on PubMed, Embase, Cochrane Library and ClinicalTrails.gov were independently searched by two investigators from inception to March 1, 2020. Review Manager software 5.3 (RevMan 5.3) was employed to calculate pooled hazard ratios (HRs), risk ratios (RRs) and 95% confidence intervals (CIs). Results: Eight studies with a total of 2605 patients were analysed. The results showed that no significant difference between IC + RT and IC + CCRT for disease-free survival (HR = 1.09, 95% CI: 0, 85–1.39, P  = 0.50), overall survival (HR = 0.92, 95% CI: 0.78–1.09, P  = 0.34), local recurrence-free survival (HR = 1.26, 95% CI: 0.95–1.67; P  = 0.10), or distant metastasis-free survival (HR = 1.03, 95% CI: 0.84–1.26, P  = 0.79). Notably, the incidence of treatment-related grade 3/4 acute haematological toxicity during radiation was higher in the IC + CCRT group. Subgroup analysis showed similar survival outcomes for IC + CCRT and IC + RT with and without the two-dimensional RT technique. Conclusions: IC + RT was as effective as IC + CCRT for the management of LA-NPC. The IC + RT regimen has the possibility of replacing the IC + CCRT regimen for LA-NPC in the future due to the lower toxicity, although more high-level evidence is urgently needed for verification.